Vaccines : mythology, ideology, and reality - Leake, John, 1970-; McCullough, Peter A. (Children's health defense., 2025)
"[The authors tell] the story of this technology and the celebrated men who developed [vaccines] with some success, but also with failures that are never mentioned in the celebratory literature on vaccines. Vaccine advocates often proclaim that they "follow the science," but most vaccine development has been a matter of guesses, gambles, and wild experimentation. Its key figures have been biased by religious faith, wishful thinking, ideology, and a desire for recognition and money. ... The authors do not dismiss the concept of vaccination but seek to promote a more informed and less dogmatic discussion about its risks and benefits"--Flap page 1 of dust jacket.